1991
DOI: 10.1143/jjap.30.l927
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Ion Yield Changes in Si due to Topography Changes during Cs+ Ion Bombardment

Abstract: Depth profiles of 30Si negative secondary ions were measured at Cs+ ion impact energies of 10.5 keV, 14.5 keV and 17.5 keV and a 45° impact angle by means of secondary ion mass spectrometry (SIMS). Yield changes due to surface topography changes occurred at 14.5 keV and 17.5 keV impact energy, although no surface topography change has ever been reported during Cs+ ion bombardment. No yield change was detected at 10.5 keV impact energy. The topography changes and ion yield changes are obviously affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The reason behind such an argument is that there cannot be a sudden change of chemical composition of the surface due to a small change in the ion incidence angle. There have been arguments and counterarguments in this regard, 11,16 but established facts seem to support this view. 17 In order to understand the effect of smoothing, ripple structures are created by 50-KeV FIB ͑the ion dose is 1 ϫ10 18 ion/cm 2 ͒ using an ion-incidence angle of 55°, and the structures are further bombarded with the FIB at smaller incidence angles.…”
Section: Resultsmentioning
confidence: 99%
“…The reason behind such an argument is that there cannot be a sudden change of chemical composition of the surface due to a small change in the ion incidence angle. There have been arguments and counterarguments in this regard, 11,16 but established facts seem to support this view. 17 In order to understand the effect of smoothing, ripple structures are created by 50-KeV FIB ͑the ion dose is 1 ϫ10 18 ion/cm 2 ͒ using an ion-incidence angle of 55°, and the structures are further bombarded with the FIB at smaller incidence angles.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have found that the yield changes exponentially in the first stages of ripple development and saturates for large sputtered depth. Direct evidence on ripple amplitude saturation was obtained by Erlebacher et al [20], who measured the time evolution of the ripple amplitude in experiments bombarding Si (100) [18,21,22], most of these studies were contradicted by subsequent investigations [23] where such chemical component were not present. Furthermore, in Refs.…”
Section: A Ripple Formationmentioning
confidence: 99%
“…While a number of attempts have been made to explain ripple formation based on chemical effects, such as O + 2 variations [18,21,22], most of these studies were contradicted by subsequent investigations [23] where such chemical component were not present. Furthermore, in Refs.…”
Section: Surface Chemistry and Other Morphological Featuresmentioning
confidence: 99%
“…Ripple formation during ion bombardment has been observed for various bombarding ions and substrates, under a wide range of sputtering conditions ͑such as ion energy and angle of incidence͒. [1][2][3][4][5][6][7][8] The numerous experimental studies have motivated theoretical investigations of the basic mechanisms responsible for the formation and evolution of ripples. [5][6][7] On the other hand, less attention has been paid to the effect of the ripples on the sputtering yield.…”
mentioning
confidence: 99%